Examining Legislative Oversight mechanisms in Afghanistan Legal System: The Manifestation of the Rule of Law - MODABER, Ali Asghar; WAMİQ, Mohammd Tariq (PEARSON JOURNAL, 2023)
The presence of regulatory mechanisms is required for the rule of law to prevent government officials and its agencies from abusing their legal authority as well as to compensate citizens for societal harms. Due to the executive’s dominance over the legislative branch in Afghanistan’s constitution and legal system, institutional, political, discretionary, informational, and financial regulatory mechanisms were unable to effectively carry out their legal obligations, thus violating the separation of powers, resulting in serious issues. Regulations cannot be used to prevent abuses by government officials as long as the separation of powers concept does not function in its genuine form.